Biochemical Characterization, Thermal Stability, and Partial Sequence of a Novel Exo-Polygalacturonase from the Thermophilic Fungus Rhizomucor pusillus A13.36 Obtained by Submerged Cultivation. (29th November 2016) - Trindade, Lucas Vinícius; Desagiacomo, Carla; Polizeli, Maria de Lourdes Teixeira de Moraes; Damasio, André Ricardo de Lima; Lima, Aline Margarete Furuyama; Gomes, Eleni; Bonilla-Rodriguez, Gustavo Orlando
Abstract : This work reports the production of an exo-polygalacturonase (exo-PG) by Rhizomucor pusillus A13.36 in submerged cultivation (SmC) in a shaker at 45°C for 96 h. A single pectinase was found and purified in order to analyze its thermal stability, by salt precipitation and hydrophobic interaction chromatography. The pectinase has an estimated Mw of approximately 43.5–47 kDa and optimum pH of 4.0 but is stable in pH ranging from 3.5 to 9.5 and has an optimum temperature of 61°C. It presents thermal stability between 30 and 60°C, has 70% activation in the presence of Ca 2+, and was tested using citrus pectin with a degree of methyl esterification (DE) of 26%. E a ( d ) for irreversible denaturation was 125.5 kJ/mol with positive variations of entropy and enthalpy for that and Δ G ( d ) values were around 50 kJ/mol. The hydrolysis of polygalacturonate was analyzed by capillary electrophoresis which displayed a pattern of sequential hydrolysis (exo). The partial identification of the primary sequence was done by MS MALDI-TOF and a comparison with data banks showed the highest identity of the sequenced fragments of exo-PG from R. pusillus with an exo-pectinase from Aspergillus fumigatus . Pectin hydrolysis showed a sigmoidal curve for the Michaelis-Menten plot.